RANCANG BANGUN BODI MOBIL LISTRIK MENGGUNAKAN FIBERGLASS - Zakaria Ramadhan; Bayu Saputra; Yasin; Yogi Prasetia; Sudarsono; Nanang Endriatno (Program Pendidikan Vokasi Teknik Mesin, 2025)
Electric cars are cars that are driven by electric motors and use electrical energy stored in batteries. The use of electric cars certainly requires a vehicle design that can meet automotive needs that are more focused on the chassis and body. The performance of electric cars is influenced by the weight and aerodynamics of the car itself, one of which is the body of the electric car, to produce good performance, a design that has a low drag coefficient value is needed so that it can cut through the wind well and make this electric car go fast. The material used to make this electric car body is fiberglass with a hand lay up application technique. In making it, several preparations are needed, namely making designs, making moulds, and making bodies using fiberglass media. The results of the study indicate that for the specifications of the car body design results, namely the body height of 60 cm, body width of 82 cm, body length of 2.73 m, upper body width of 63 cm, inner body width of 50 cm, front body height of 37 cm, body glass length of 101 cm, glass width of 63 cm, rear glass height of 44.5 cm, front glass height of 10.5 cm with a body weight of 19.25 kg and a glass weight of 2.15 kg. The conclusion of this study is that the prototype body of the electric car can be attached to the frame properly after the car is used or driven and the prototype body. Electric cars are made of fiberglass, this material is very appropriate because it has a light character, easy to shape. But for performance in electric cars, body weight greatly affects the speed of electric cars so it is hoped that further research will be developed with a lighter form of electric car body.